Model Komunikasi Pemeriksaan Dalam Sidang Agenda Pembuktian Perkara di Pengadilan - Widodo, Aan (Jurnal Komunikasi, 2020)
An examination of the case is conducted to reveal evidence and information that the defendant is considered to have committed a criminal offense that caused the victim to loss, and that the victim is the party who was harmed by the defendant. Case examination through communication activities in the case examination agenda session as examination communication. This article aims to find a model of examination communication in the agenda of proving a case in court. The concept in this research is Examination Communication and Communication Ethnography. The research method used is descriptive qualitative research. Researchers interviewed 15 informants, observed 3 criminal cases, and documented the research. The results of this study indicate that the audit communication activities at the Court take place in the courtroom. The case evidence agenda forms three models of examination communication based on communication participants, namely (1) the law enforcement communication model with the defendant, namely the communication activities of judges, prosecutors, and legal advisers with the defendant (2) law enforcer communication model with victims, namely communication activities of judges , legal advisers, public prosecutors with victims (3) the model of communication between law enforcers and witnesses, namely the communication activities of judges, legal advisers, prosecutors with defendants. In practice, communication activities for the examination of defendants, victims and witnesses can be carried out simultaneously, which is called the cross examination communication model. The cross-examination communication model is carried out to verify and confirm evidence, the information provided by the accused, witnesses and victims simultaneously. Pemeriksaan perkara dilakukan untuk mengungkap bukti dan informasi bahwa terdakwadianggap melakukan tindak pidana yang merugikan korban, dan bahwa korban adalah pihak yang dirugikan oleh terdakwa. Pemeriksaan perkara melalui kegiatan komunikasi dalam sidang agenda pemeriksaan perkara sebagai komunikasi pemeriksaan. Artikel ini bertujuan untuk menemukan model komunikasi pemeriksaan dalam agenda pembuktian perkara di Pengadilan. Konsep dalam penelitian ini adalah Komunikasi Pemeriksaan dan Etnografi Komunikasi. Metode penelitian yang digunakan adalah penelitian deskriptif kualitatif. Peneliti mewawancarai 15 informan, mengamati 3 kasus pidana, dan mendokumentasikan penelitian tersebut. Hasil penelitian ini menunjukkan bahwa kegiatan komunikasi pemeriksaan di pengadilan berlangsung di ruang sidang persidangan. Agenda pembuktian perkara membentuk tiga model komunikasi pemeriksaan berdasarkan peserta komunikasi, yaitu (1) model komunikasi penegak hukum dengan terdakwa, yaitu kegiatan komunikasi para hakim, jaksa, dan penasihat hukum dengan terdakwa (2) model komunikasi penegak hukum dengan korban, yakni kegiatan komunikasi hakim, penasihat hukum, penuntut umum dengan korban (3) model komunikasi antara penegak hukum dan saksi yakni kegiatan komunikasi hakim, penasihat hukum, jaksa, dengan terdakwa. Dalam praktiknya, kegiatan komunikasi pemeriksaan terdakwa, korban, dan saksi dapat dilakukan secara bersamaan, yang disebut model komunikasi pemeriksaan silang. Model komunikasi pemeriksaan silang dilakukan untuk memverifikasi dan mengkonfirmasi bukti, informasi yang diberikan oleh terdakwa, saksi dan korban secara bersamaan.